Aortic atherosclerotic plaques: the role of anticoagulation. (14th October 2021) - Silverio Antonio, P; Rodrigues, T; Cunha, N; Couto Pereira, S; Brito, J; Valente Silva, B; Alves Da Silva, P; Beatriz Garcia, B; Martins, M; Oliveira, C; David, C; Caldeira, D; et al.
Abstract: Introduction: Aortic atherosclerotic plaques (AAPs) are one of the major causes of spontaneous and iatrogenic stroke and peripheral emboli, carrying an high morbidity and mortality. Transoesophageal echocardiography (TOE) plays a key rule on detecting AAP. The therapeutic approach of this patients (pts) is not well stablished. Purpose: To evaluate the impact of anticoagulation (ACO) therapy on major events in asymptomatic pts with AAP detected in TOE. Methods: Single-center retrospective study of consecutive patients submitted to TOE between 2010 and 2019 with documentation of AAP. Plaques were described as complex (1) >4mm, (2) ulcerated and (3) mobile thrombi. The plaque location was also documented. We consulted pts data charts for clinical characterization and events recording during the follow up. Major events were defined as stroke, bleeding, hospital admissions (either cardiovascular (CV) and non-CV) and death. Statistical analysis was performed using Cox regression and Chi-square tests. Results: We enrolled 177 pts with a mean age of 70±10.5 years, 63.8% males, 31.1% diabetic, 73.4% hypertensive, 54.2% with dyslipidaemia, 62.7% obese, 25.4% with peripheral arterial disease, 25.9% with previous stroke and 55.4% with supraventricular arrhythmia. Most of pts had plaques >4mm (80.8%), mobile thrombi in 11.9% and ulcerated plaques in 7.3%; most of the plaques were located in proximal descending aorta (50.3%) and aortic cross (38.4%). Regarding baseline therapy, 52% were under ACO and 50.3% under statin. The main indication of ACO was atrial fibrillation (45.8%). During follow up (mean time: 1613±1255 days), 61.5% pts died (10.7% from CV causes, 13% with unknown cause), 17.5% had a stroke, 5.7% had other embolic event (lower limbs emboli, unilateral amaurosis and ischemic colitis). Bleeding occurred in 18.3% pts; 47% pts were hospitalized (28.3% from CV cause). Adjusting for age and comorbidities, there were no significant differences between the group with and without ACO. ACO therapy prevented death from any cause, being also an independent predictor (p=0.08, OR 0.489, IC 95% 0.288–0.831) when adjusted for comorbidities and age. ACO was associated with bleeding events (p=0.003), but not with stroke or hospitalization from any cause (p=NS). Conclusion: In this subset of pts, ACO therapy prevented death from any cause in pts with AAP. This may have therapeutic implications when approaching this pts, although larger studies to confirm these results are needed. Funding Acknowledgement: Type of funding sources: None.